EFL Students' Perception of Character AI as a Tool to Improve Their Writing Skills: A Qualitative Study - Fadhila, Fadhila; Kembaren, Farida Repelita Waty Br. (Nusantara: Jurnal Pendidikan Indonesia, 2025)
Purpose – This article aims to explain students' perspectives toward Character AI and how Character AI helps them develop their writing skills and confidence in writing.Method – This article employs a qualitative case study to gather data through questionnaires and interviews, aiming to understand the respondents' perspectives on the application. Findings – The participants concluded that Character AI aids in writing skills by helping them learn new sentences, improve grammar, and understand context, ultimately boosting self-confidence. Survey results show that 33.3% found Character AI significantly contributed to their English sentence acquisition, while 66.7% experienced some linguistic benefits. In terms of grammatical improvement, 33.3% rated it highly effective, 44.4% noted moderate efficacy, and 22.2% reported minimal enhancement. Regarding writing confidence, 33.3% experienced a significant decline, 55.6% a moderate decrease, and 11.1% a marginal drop. Research Implications – This study highlights the potential of artificial intelligence in education, particularly in enhancing students' writing skills. Through questionnaires and interviews, it was found that character AI significantly impacts students' ability to learn new sentences, correct grammar, and understand context, while also boosting their confidence in writing. The research utilized a quantitative methodology with a larger participant group to validate these findings. However, further studies are necessary to explore the real effects of character AI on students' writing, as this technology is still new to them.